First isolation and sequencing of rabies virus detected in a red fox in Albania - L. Lufo; E. Picard-Meyer; E. Robardet; V. Shtjefni; F. Cliquet; P. Koli; P. Çobo (Bulgarian Journal of Veterinary Medicine)
Rabies has been an endemic disease in Albania. From time to time, positive cases have been recorded in wild and domestic animals, and occasionally in humans. Passive surveillance is the main method used by veterinary and health authorities to monitor the incidence of the disease and organise preven-tion and treatment in case of exposure. The last detection of rabies virus (RABV) in the country was recorded in 2014 from a red fox in Kukes District, North of Albania. In the same year 2 other samples (1 from a red fox and 1 from a shepherd dog), originated from the same area and were reported and analysed but rabies virus was not detected. Methods used for antigen detection and virus isolation were the fluorescent antibody test (FAT) and the rabies tissue culture infection test (RTCIT), respec-tively. Typing of rabies virus isolate was done using SANGER sequencing. A real-time RT PCR method was performed before genetic characterisation. The genetic analyses showed that this field strain, DR914 fox 2014 ALBANIA, belonged to the same EE group of isolates from neighbouring countries of the Republic of North Macedonia, Montenegro, Greece, and Serbia. DR914 fox 2014 Albania is the last rabies virus isolated and sequenced in Albania. Increased surveillance and related molecular epidemiology research are needed to get a complete understanding of the phylogeny and evolution of the rabies virus in the Balkan region.